Herpetología patagónica : VI. Los Liolaemus del grupo Fitzingeri en Santa Cruz y Chubut (Sauria, Iguanidae) - Cei, José Miguel Alfredo María (1973)
Ecological and morphological features of patagonian populations of Liolaemus fitzingeri are analyzed and discussed. The close serological relationships between different samples from Santa Cruz and Chubut provinces are pointed out. Two well defined geographical forms are recognized, in accordance with several significant morphological differences : Liolaemus fitzingeri fitzingeri (Dum. et Bibr.) from southern Chubut and S. Cm2, and Liolaemus fitzingeri melanops (Burmeister) from the borders of the basaltic meseta of Canquel, south Chubut River. A wide zone of sandy salt fiats may be assumed as a probable natural barrier of isolation betweeu these forms.